PENGARUH DEBT TO EQUITY RATIO (DER) DAN GROSS PROFIT MARGIN (GPM) TERHADAP PERTUMBUHAN LABA PADA PT. ASTRA INTERNATIONAL Tbk PERIODE 2014-2023 - Astri Wardani, Nicky; Sulistyani, Tri (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine partial and simultan effect of Debt to Equity Ratio (DER) and Gross Profit Margin (GPM) on Earnings Persistence at PT Astra Internasional Tbk for the period 2014-2023. The research method used in this research is descriptive quantitative research to determine the effect of Debt to Equity Ratio (DER) and Gross Profit Margin (GPM) on Earnings Persistence partially or simultaneously. The population used in this study is the financial statements of PT Astra Internasional Tbk in the period 2014-2023. Based on the results of research that has been carried out, it is concluded that, 1) Debt to Equity Ratio (DER) has a negative and insignificant effect on Return On Assets (ROA), 2) Gross Profit Margin (GPM) has a possitive and insignificant effect on Return On Assets (ROA). ), 3) Debt to Equity Ratio (DER) and Gross Profit Margin (GPM) have a positive and insignificant effect on Earnings Persistence. This can be seen from the R Square of 0.174 or 17.4%, which means that the Debt to Equity Ratio (DER) and Gross Profit Margin (GPM) only have effect of 17.4% on Earnings Persistence, while 82.6% is influenced by other variables outside of this study.